2014
DOI: 10.1167/14.5.14
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of the pupillary response to luminance and color changes during interocular suppression

Abstract: The present study investigated the effects of interocular suppression on the pupillary constriction to luminance and color changes. Stable interocular suppression was produced by presenting a flickering high-contrast grating to one eye and a spatially homogeneous field to the other eye. The results showed that the pupillary responses to luminance as well as color changes were clearly attenuated during interocular suppression; the pupillary constriction to stimulus changes was delayed and reduced in amplitude w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…This kind of constriction is similar in size, but opposite in sign, to the engagement-related dilation mentioned above (about 0.1 to 1 mm in diameter; Slooter & van Norren 1980;Barbur et al 1992;Young et al 1993;Conway et al 2008), matching our finding of similar magnitudes for both our positive and our negative rapid response component. Several lines of evidence suggest a cortical contribution to constrictions in response to isoluminant input transients: these constrictions are virtually abolished by cortical lesions (Barbur et al 1992;Heywood et al 1998), and they are modulated by attention withdrawal and interocular suppression (Kimura et al 2014;Kaneko et al 2019), as well as by stimulus properties that lack a specific representation outside of cortex (e.g. the orientation of a viewed face; Conway et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This kind of constriction is similar in size, but opposite in sign, to the engagement-related dilation mentioned above (about 0.1 to 1 mm in diameter; Slooter & van Norren 1980;Barbur et al 1992;Young et al 1993;Conway et al 2008), matching our finding of similar magnitudes for both our positive and our negative rapid response component. Several lines of evidence suggest a cortical contribution to constrictions in response to isoluminant input transients: these constrictions are virtually abolished by cortical lesions (Barbur et al 1992;Heywood et al 1998), and they are modulated by attention withdrawal and interocular suppression (Kimura et al 2014;Kaneko et al 2019), as well as by stimulus properties that lack a specific representation outside of cortex (e.g. the orientation of a viewed face; Conway et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Several elegant studies using binocular rivalry, dating back almost a century, already revealed cognitive influeces on the pupil light response (Bárány & Halldén, 1948; Brenner, Charles, & Flynn, 1969; Harms, 1937; Lowe & Ogle, 1966; for recent replications, see Fahle, Stemmler, & Spang, 2011; Kimura, Abe, & Goryo, 2014; Naber, Frassle, & Einhauser, 2011). For example, Bárány & Halldén (1948) presented a horizontal line to one eye, and a vertical line to the other eye.…”
Section: The Pupil Light Responsementioning
confidence: 99%
“…The long-lasting, sustained pupil dilation response reflecting arousal may be different from the fast, transient component that presumably reflects other cognitive states and thus affect the feeling of attractiveness. Indeed, other studies showed that pupils in general quickly constrict in response to the mere onset of visual presentation (even when the mean luminance is equated, e.g., Kimura, Abe, & Goryo, 2014) and that this early and reflexive pupillary constriction response is modulated by various cognitive factors such as memory (Naber et al, 2013), attention (Binda, Pereverzeva, & Murray, 2013Mathôt, Dalmaijer, Grainger, & Van der Stigchel, 2014;Mathôt, van der Linden, Grainger, & Vitu, 2013), and perceptual brightness when the physical luminance is kept the same (Suzuki, Minami, Laeng, & Nakauchi, 2019;Laeng & Endestad, 2012). For instance, in Naber et al (2013), participants were asked to memorize various natural scene images presented one by one (memorization phase) to recall later in the retrieval phase.…”
Section: Introductionmentioning
confidence: 99%